Realizing farmers’ rights through community-based agricultural biodiversity management - Clancy, Evelyn; Vernooy, Ronnie (Bioversity International, 2016)
This brief has been prepared by Bioversity International for delegates to the 2016 Global Consultation on Farmers’ Rights. The brief aims to raise awareness among delegates and Contracting Parties to the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) of the crucial contribution that a community-based approach to the conservation and sustainable use of agricultural biodiversity can make to realizing farmers’ rights and empowering men and women smallholder farmers. At the Sixth Session of the Governing Body, under Resolution 5/2015, the Secretariat was requested “to engage Contracting Parties and relevant organizations to take initiatives to gather information at national, regional and global levels for exchanging views, experiences and best practices on the implementation of Farmers’ Rights”. This brief aims to contribute to that body of information.